Performance of Introducing Outdoor Cold Air for Cooling a Plant Production System with Artificial Light - Wang, Jun; Tong, Yuxin; Yang, Qichang; Xin, Min (Frontiers in Plant Science, 2016)
The commercial use of a plant production system with artificial light (PPAL) is limited by its high initial construction and operation costs. The electric-energy consumed by heat pumps, applied mainly for cooling, accounts for 15-35% of the total electric-energy used in a PPAL. To reduce the electric-energy consumption, an air exchanger with low capacity (180 W) was used for cooling by introducing outdoor cold air. In this experiment, the indoor air temperature in two PPALs (floor area: 6.2 m2 each) was maintained at 25ºC and 20ºC during light and dark periods, respectively, for lettuce production. In one PPAL (PPALe), an air exchanger (air flow rate: 250 m3 h-1) was used along with a heat pump (cooling capacity: 3.2 kW) to maintain the indoor air temperature at the set-point. The other PPAL (PPALc) with only a heat pump (cooling capacity: 3.2 kW) was used for reference. Effects of introducing outdoor cold air on energy use efficiency, coefficient of performance (COP), electric-energy consumption for cooling and growth of lettuce were investigated. The results show that: when the air temperature difference between indoor and outdoor ranged from 20.2°C to 30.0°C: 1) the average energy use efficiency of the air exchanger was 2.8 and 3.4 times greater than the COP of the heat pumps in the PPALe and PPALc, respectively; 2) hourly electric-energy consumption in the PPALe reduced by 15.8-73.7% compared with that in the PPALc; 3) daily supply of CO2 in the PPALe reduced from 0.15 kg to 0.04 kg compared with that in the PPALc; 4) no significant difference in lettuce growth was observed in both PPALs. The results indicate that using air exchanger to introduce outdoor cold air should be considered as an effective way to reduce electric-energy consumption for cooling with little effects on plant growth in a PPAL.